Essere giudice - Caso, Francesco (Ledizioni, 2018)
A brief political-existential essay, "Essere giudice" addresses the basic theme of the judge faced with the challenges of modernity, without any preceptive or pedagogical pretence. It is divided into ten chapters, each of which tries to answer a question: "Why is one a judge?" "Where is one a judge?" "When is one a judge?" "How long is one a judge?" "With whom is one a judge?" "With what means is one a judge?" "For whom is one a judge?" "How is one a judge?" "In what functions is one a judge?" and finally "Who is a judge?". It is up to the reader to determine whether the answers found by Francesco Caso have any value, if only for the fact that they have been attempted, perhaps for the first time.